Antioxidant and dual dose-dependent antigenotoxic and genotoxic properties of an ethanol extract of propolis - Cruz, M. (2020)
Propolis is a resinous product made by honeybees from plant-derived materials, with high content ofpolyphenols associated to several beneficial bioactivities with potential use as a natural food additive forpreservation and as a functional food ingredient. A Portuguese propolis ethanol extract (C.EE) protectedSaccharomyces cerevisiaecells from loss of viability upon exposure to H2O2, both in co- and in pre-incubation experiments. Results obtained with the comet assay suggest that lower concentrations areantigenotoxic while at higher concentrations a genotoxic effect prevails, which correlates with thecytotoxicity of high concentrations of C.EE. Flow cytometry analysis with dichlorofluorescein indicatesthat C.EE induced intracellular antioxidant activityin vivo. Overall the results suggest that C.EE isantigenotoxic but is also toxic at higher concentrations. This dual effect could be explained by thepresence of compounds known to interfere with DNA synthesis and/or cell proliferation, such as caffeicacid phenethyl ester (CAPE) and chrysin, together with antioxidants, like kaempferol, pinobanksin andpinocembrin.